International Recruitment: Oversight and Standards - Engberg, David (International Higher Education, 2013)
U.S. institutions are increasingly using paid agents to recruit international students. This article examines competing perspectives regarding this practice, reviews one organization's efforts to provide quality assurance and oversight of international agents, and argues that institutions need to develop their own policies and practices before initiating any agency relationships.